Age of depositional and weathering events in Central Amazonia. (15th August 2017) - Sant'Anna, Lucy Gomes; Soares, Emílio Alberto do Amaral; Riccomini, Claudio; Tatumi, Sonia Hatsue; Yee, Marcio
Abstract: In the last three decades, several studies have been devoted to understanding the role of Late Pleistocene–Holocene climate changes in the Amazonia lowlands environment. However, most of these studies used data obtained from sedimentary deposits (lakes, swamps, and colluvium) located away from the central plain or on the edges of the Amazonia region. This article integrates optically stimulated luminescence and accelerated mass spectrometry 14 C ages with sedimentological and geomorphological data obtained during this study or compiled from the literature for fluvial and lacustrine deposits of the central alluvial plain of the Solimões-Amazon River. The age data allow us to present a chronological framework for the Late Pleistocene–Holocene deposits and conclude that (i) the dryness of the LGM in central Amazonia lowlands is recorded by the formation of fluvial terraces and their weathering to pedogenic hematite between 25.3 ka and 17.7 ka; (ii) floodplain deposition was contemporaneous with terrace weathering and occurred in a context of decreased water volume in fluvial channels, lowering of river base level and sea level, and isostatic rebound of the continent; and (iii) lateral and mid-channel fluvial bars in the Solimões-Amazon River have a minimum age of 11.5 ± 1.5 ka, and their deposition responded to increased precipitation at the beginning of the Holocene. Highlights: Fluvial deposits of the Solimões-Amazon River in central Amazonia lowlands were dated by OSL and AMS 14 C. Dryness of LGM recorded by weathered fluvial deposits dated of 25.3–17.7 ka, contemporaneous to floodplain deposition. Deposition of large fluvial bars in the Solimões-Amazon River started at least at the Pleistocene-Holocene boundary.